A Specialised Translation Approach in ESP Classrooms: The Role of the L1 in Teaching and Learning the L2 - Boukranaa, Ahmed; Mjahad, Rania (Technium Social Sciences Journal, 2025)
The employment of specialised translation for teaching English has attracted significant attention. Modern research has proven that specialised translation is operative in ESP lessons. This paper investigates academic publications based on the study of translation's effects on ESP learners. Inductive Thematic analysis was used to investigate a corpus of 30 research articles. The academic publications under investigation were selected through systematic literature research from different academic platforms such as Google Scholar, Zenodo, Academia, Researchgate, Clarivate, Elsevier and others. The inductive thematic analysis aided in uncovering themes associated with the teaching practices, translation activities and the learner's level, designing courses, administrative and academic instructions, enhancing language accuracy, and the communicative role of translation, enlarging the learners' lexical repertoire and consolidating comprehension skills. Integrating translation activities in ESP classes significantly enhances the four skills and allows translation to become a Fifth skill. The findings of this paper indicate that implementing specialised translation in ESP lessons is a fundamental matter that EFL professionals must consider.